23rd International Symposium on Principles and Practice of Declarative Programming 2021
DOI: 10.1145/3479394.3479403
|View full text |Cite
|
Sign up to set email alerts
|

Confluence in Non-Left-Linear Untyped Higher-Order Rewrite Theories

Abstract: We develop techniques based on van Oostrom's decreasing diagrams that reduce confluence proofs to the checking of critical pairs for higher-order rewrite rules extending beta-reduction on pure lambda-terms. We show that confluence is preserved for a large subset of terms that contains all pure lambda terms. Our results are applied to famous Klop's examples of non-confluent behaviours in presence of convergent rewrite rules and to fragments of various encodings, in a dependent type theory with rewrite rules, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…We have therefore shown that the theory of global states preserves the confluence of -reductions on all untyped terms, hence improving over (Ferey and Jouannaud 2019), by using the order on rules’ labels inherited from the decision to have ll and uu as small rules. This example could actually not be shown confluent with an empty set of small rules, as can be checked by the reader, because, in that case, there would be additional infinite families whose joinability diagram would require to be decreasing, while the existing infinite families require just the contrary.…”
Section: Confluence Inmentioning
confidence: 88%
See 4 more Smart Citations
“…We have therefore shown that the theory of global states preserves the confluence of -reductions on all untyped terms, hence improving over (Ferey and Jouannaud 2019), by using the order on rules’ labels inherited from the decision to have ll and uu as small rules. This example could actually not be shown confluent with an empty set of small rules, as can be checked by the reader, because, in that case, there would be additional infinite families whose joinability diagram would require to be decreasing, while the existing infinite families require just the contrary.…”
Section: Confluence Inmentioning
confidence: 88%
“… is a mix of the annotated lambda-calculus and Klop’s combinatory reduction systems (Klop 1980) which extends the calculus introduced in (Ferey and Jouannaud 2019) by having annotated abstractions to faithfully abstract dependently typed calculi whose confluence properties are our real target.…”
Section: Computational Modelmentioning
confidence: 99%
See 3 more Smart Citations